Answer:
6x^2 (3x^2 - 2)
Step-by-step explanation:
18x^4 - 12x^2
6x^2 (3x^2 - 2)
Answer:
and the question is? I'm confused
Answer:
![k=\pm 6](https://tex.z-dn.net/?f=k%3D%5Cpm%206)
Step-by-step explanation:
The given quadratic equation is :
![x^2 - kx + 8 = 0](https://tex.z-dn.net/?f=x%5E2%20-%20kx%20%2B%208%20%3D%200)
One of the roots of this equation is twice that of the other. Let the roots are
, ![\alpha =2\beta](https://tex.z-dn.net/?f=%5Calpha%20%3D2%5Cbeta)
Sum of roots, ![\alpha +\beta =\dfrac{-b}{a}](https://tex.z-dn.net/?f=%5Calpha%20%2B%5Cbeta%20%3D%5Cdfrac%7B-b%7D%7Ba%7D)
![\alpha +\beta =\dfrac{-(-k)}{1}\\\\\alpha +\beta =k\\\\3\beta =k\ .......(1)](https://tex.z-dn.net/?f=%5Calpha%20%2B%5Cbeta%20%3D%5Cdfrac%7B-%28-k%29%7D%7B1%7D%5C%5C%5C%5C%5Calpha%20%2B%5Cbeta%20%3Dk%5C%5C%5C%5C3%5Cbeta%20%3Dk%5C%20.......%281%29)
Product of roots,
![\alpha \beta =\dfrac{c}{a}\\\\2\beta ^2=\dfrac{8}{1}\\\\\beta =\pm 2](https://tex.z-dn.net/?f=%5Calpha%20%5Cbeta%20%3D%5Cdfrac%7Bc%7D%7Ba%7D%5C%5C%5C%5C2%5Cbeta%20%5E2%3D%5Cdfrac%7B8%7D%7B1%7D%5C%5C%5C%5C%5Cbeta%20%3D%5Cpm%202)
If
,
![k=3(2)\\\\=\pm 6](https://tex.z-dn.net/?f=k%3D3%282%29%5C%5C%5C%5C%3D%5Cpm%206)
So, the value of k is equal to
.